Identification of Dietzia spp. from Cardiac Tissue by 16S rRNA PCR in a Patient with Culture-Negative Device-Associated Endocarditis: A Case Report and Review of the Literature - Praveen Sudhindra; Guiqing Wang; Robert B. Nadelman (Case Reports in Infectious Diseases)
The genus Dietzia was recently distinguished from other actinomycetes such as Rhodococcus. While these organisms are known to be distributed widely in the environment, over the past decade several novel species have been described and isolated from human clinical specimens. Here we describe the identification of Dietzia natronolimnaea/D. cercidiphylli by PCR amplification and sequencing of the 16S rRNA encoding gene from cardiac tissue in a patient with culture-negative device-associated endocarditis.